The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/es101554m
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structure in Geographically Distributed Biological Wastewater Treatment Reactors

Abstract: Current knowledge of the microbial communities within biological wastewater treatment reactors is incomplete due to limitations of traditional culture-based techniques and despite the emergence of recently applied molecular techniques. Here we demonstrate the application of high-density microarrays targeting universal 16S rRNA genes to evaluate microbial community composition in five biological wastewater treatment reactors in China and the United States. Results suggest a surprisingly consistent composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
72
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(100 citation statements)
references
References 29 publications
(37 reference statements)
22
72
2
2
Order By: Relevance
“…Except for the four Hong Kong sludge samples, which had the a-subdivision as the most dominant class within Proteobacteria, in all other 11 samples, the b-subdivision was the most dominant Proteobacteria, followed by a-, g-and d-subdivisions. This is different from results of a study using microarray (Xia et al, 2010), which showed that a-subdivision was the most abundant of the Proteobacteria. However, the findings are similar to the results of another study about soil bacteria using pyrosequencing (Roesch et al, 2007), which demonstrated that in most soils, the b-subdivision was the most abundant one within the Proteobacteria.…”
Section: Diversity Of Microbial Communitiescontrasting
confidence: 99%
See 1 more Smart Citation
“…Except for the four Hong Kong sludge samples, which had the a-subdivision as the most dominant class within Proteobacteria, in all other 11 samples, the b-subdivision was the most dominant Proteobacteria, followed by a-, g-and d-subdivisions. This is different from results of a study using microarray (Xia et al, 2010), which showed that a-subdivision was the most abundant of the Proteobacteria. However, the findings are similar to the results of another study about soil bacteria using pyrosequencing (Roesch et al, 2007), which demonstrated that in most soils, the b-subdivision was the most abundant one within the Proteobacteria.…”
Section: Diversity Of Microbial Communitiescontrasting
confidence: 99%
“…The other dominant phyla were Firmicutes (1.4-14.6%, averaging at 8.1%), Bacteroidetes (2.7-15.6%, averaging at 7.0%) and Actinobacteria (1.3-14.0%, averaging at 6.5%). Similar to a few previous studies on AS using microarray (Xia et al, 2010) and cloning (Snaidr et al, 1997), these four groups were dominant (56-86%) in bacterial communities of the 15 AS samples in this study, followed by a few other major (average abundance 41%) phyla, including Verrucomicrobia (4.2%), Chloroflexi (3.4%), Acidobacteria (3.0%) and Planctomycetes (2.4%). A few phyla, including TM7, Thermotogae, OD1, Spirochaetes, WS3, Nitrospira and Synergistetes, were only the major (abundance 41%) phyla in one of the 15 samples.…”
Section: Diversity Of Microbial Communitiessupporting
confidence: 89%
“…They have suggested that microbial populations showed a surprisingly consistent composition within wastewater treatment systems at different geographic locations (Xia et al 2010;Wang et al 2012a) and indicated higher microbial similarities (higher Jaccard's similarity coefficients) of the WWTPs in the same city (Wang et al 2012a). Geographic location has been reported to be the most important factor shaping bacterial communities especially nonfecal groups in untreated sewage (Shanks et al 2013).…”
Section: Similarity Of Microbial Communitiesmentioning
confidence: 99%
“…Despite the microbiological methods used, plenty of the studies on microbial communities of activated sludge bioreactors have been conducted to profile taxonomic information based on 16S rRNA genes, using technical approaches of clone library (Wells et al 2011;Yang et al 2011), denaturing gradient gel electrophoresis (DGGE) (Yang et al 2011), terminal restriction fragment length polymorphism (T-RELP) (Wells et al 2011;Yang et al 2011), fluorescence in situ hybridization (FISH) (Mielczarek et al 2012(Mielczarek et al , 2013, Illumina (Albertsen et al 2012), 454-pyrosequencing (Hu et al 2012;Wang et al 2012a), and PhyloChips (Xia et al 2010). However, 16S rRNA gene-based ways may not be efficient in distinguishing some closely related but ecologically distinct groups of microorganisms as a consequence of the low evolutionary rate of 16S rRNA genes (Palys et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Three oligonucleotide probes complementary to the 16S rRNAs of Z. ramigera ATCC 19544 were designed to detect the bacterial cells that accumulated in the typical branched gelatinous matrices, the so-called Zoogloea fingers (Wagner et al, 1993;Rossello-Mora et al, 1995) and it was shown that Zoogloea cells accounted for up to approximately 10% of the total cell numbers. The 16S rRNA gene clone library sequencing showed that Proteobacteria was the largest phylum in the activated sludge (Snaidr et al, 1997) and the PhyloChip microarray analyses further revealed that Proteobacteria was the predominant phylum, followed by Firmicutes, Actinobacteria and Bacteroidetes (Xia et al, 2010). As revealed by high throughput 454 pyrosequencing of amplicons, Zoogloea was one of the dominant genera and existed in high abundance (1.38e11.1%) in most of the AS samples from the municipal sewage treatment plants of mainland China, Hong Kong, Singapore, Canada, and United States (Zhang et al, 2012;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%